2016
DOI: 10.1007/s11187-016-9763-4
|View full text |Cite
|
Sign up to set email alerts
|

Family business going abroad: the effect of family ownership on foreign market entry mode decisions

Abstract: Research on family firms’ internationalization\ud is growing, but empirical findings are mixed.\ud To reconcile prior studies, we focus on strategic\ud decisions related to internationalization, specifically\ud the foreign market entry mode selection process. We\ud suggest that the choice about entry mode is especially\ud significant for family owners because it may either\ud align or conflict with two key family-related goals:\ud maintaining family control and keeping a long-term\ud orientation of the busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 57 publications
2
42
0
1
Order By: Relevance
“…partnering with another company), desiring to avoid limiting control of their business (Pongelli et al . ). Research further suggests that family businesses pursuing the goal of transgenerational control have a higher perceived selling price for their firm (Zellweger et al .…”
Section: Review Of Family Business Goals Literaturementioning
confidence: 97%
“…partnering with another company), desiring to avoid limiting control of their business (Pongelli et al . ). Research further suggests that family businesses pursuing the goal of transgenerational control have a higher perceived selling price for their firm (Zellweger et al .…”
Section: Review Of Family Business Goals Literaturementioning
confidence: 97%
“…This leaves considerable room to investigate the role of family heterogeneity and whether and how family ownership and control affect other relevant internationalization dimensions, such as choice of entry mode (Boellis, Mariotti, Minichilli, & Piscitello, 2016;Chang, Kao, & Kuo, 2014;Kuo, Kao, Chang, & Chiu, 2012. Liang, Wang, & Cui, 2014Pongelli, Caroli, & Cucculelli, 2016), and internationalization speed (Lin, 2012).…”
Section: Internationalization Of Family Firms: the Key Role Of Hetementioning
confidence: 99%
“…The perceived benefits of such partnerships are controversial, but in the sampled cases (Nakos et al, 2014), succeeded due to the mutually beneficial terms of the IJVs. Again, these findings clearly indicate a loss of control, even to an unknown partner, is acceptable for family firms, when the long-term survival of the firm is secured (Pongelli et al, 2016), as summarized in Proposition 6: Proposition 6. Family firm principals mainly motivated to leverage their IJV partner for market/network access choose them among strangers (based on pre-defined criteria).…”
Section: Proposition 5 Captures This Finding Belowmentioning
confidence: 83%
“…With regards to equity entry modes, family firms are found to lean towards WOS (Boellis et al, 2016) as they allow the owning-family to preserve family control and influence (Arregle et al, 2019;Claver et al, 2008;Gómez-Mejía et al, 2007). The formation of an IJV is genuinely seen as breaking with the dominant logic of family firms, who aim at keeping control and influence in the family, although economically it could be the most rational choice (Pongelli et al, 2016). Nonetheless, few recent studies found evidence that an unfamiliar culture in the target market might still motivate family firms to consider an the entry mode of an IJV to overcome the perceived barriers (Kao et al, 2013).…”
Section: Family Firm Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation